2021
DOI: 10.1371/journal.pone.0251735
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy among paediatric nurses: Prevalence and associated factors

Abstract: Objective This study describes the prevalence of vaccine hesitancy associated with the Catalan systematic childhood vaccination calendar and some related psychosocial determinants among paediatric primary care nurses in Barcelona (Spain). Methods Cross-sectional descriptive study. In 2017 we invited the paediatric nurses (N = 165) working in Barcelona public primary health centres with paediatric departments (N = 41) to participate. They answered a questionnaire with sociodemographic and behavioural variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
2
17
0
2
Order By: Relevance
“…Demographic factors among HCWs such as male gender, greater age, and attainment of a doctoral degree were positively associated with acceptance of COVID-19 vaccines 40 . Our findings align with prior reports of higher rates of vaccine acceptance among physicians compared to nurses [41][42][43][44] . Among hesitant respondents in this survey, the advice of their physician improved willingness to accept a COVID-19 vaccine, as did recommendation by their employer, to a lesser extent.…”
Section: Discussionsupporting
confidence: 91%
“…Demographic factors among HCWs such as male gender, greater age, and attainment of a doctoral degree were positively associated with acceptance of COVID-19 vaccines 40 . Our findings align with prior reports of higher rates of vaccine acceptance among physicians compared to nurses [41][42][43][44] . Among hesitant respondents in this survey, the advice of their physician improved willingness to accept a COVID-19 vaccine, as did recommendation by their employer, to a lesser extent.…”
Section: Discussionsupporting
confidence: 91%
“…Whilst physicians have long been considered one of the most adherent professional categories towards flu vaccination [ 47 ], even without reaching the optimal coverage target [ 48 ], results from residents and nurses might be considered more surprising. Particularly, despite a long tradition of vaccine hesitancy found in the scientific literature for nurses [ 11 , 49 ], this professional group nearly tripled among the vaccinated population in the 2020–2021 campaign [ 25 ]. Concerning residents, our study showed their leading role in the 2021–2022 campaign, as the number of those who received flu vaccination nearly doubled.…”
Section: Discussionmentioning
confidence: 99%
“…25 Our study aligns with similarly recorded trends of higher rates of vaccination acceptance among physicians compared to nurses. [26][27][28][29] Among hesitant respondents in this survey, the advice of their physician was the factor most likely to change their minds, followed by the recommendation of their employer. This effect could be amplified if the physician had personally received the vaccine.…”
Section: Discussionmentioning
confidence: 99%